Pengaruh Website Quality terhadap Perceived Trust dan Dampaknya pada Repurchase Intention pada Website Matahari Mall - Freddy Sudiyono; Chairy Chairy (Universitas Tarumanagara, 2022)
The purpose of this study was to determine the effect website quality to perceive trust and its impact to repurchase intention with website brand and perceive value as the moderate variables. This is explanatory type of research, using partial least square (sem-pls) analysis technique which is measured with the help of SmartPLS 3.0 software. Data collection method is by distributing questionnaires with probablity sampling techniques taken from the unknown population of Matahari Mall website visitors, questionnaires is distributed during the time period of may to august 2017 so that been collected the number of 100 respondents who deployed in may 2017. The results of this study indicate a significant and positive direct effect of website quality and perceive trust on repurchase intention of Matahari Mall website. Perceive value also have significant impact of moderating the relation between perceive trust and repurchase intention. More over website quality has the biggest impact directly on repurchase intention. Advice that given to the Matahari Mall website is firstly to improve website quality through product content and decription evaluation and make the rules for business partner about standard of product content and description information, and they have to improve the supervision of website content and description information.